Islamic Legal Literacy of Millennial Preachers on Social Media: Between Religious Authority, Digital Popularity, and Contemporary Dakwah Challenges : (A Case Study in West Sumatra) - Nanang Arianto; Elva Mahmudi; Vito Dasrianto (DAWUH : Islamic Communication Journal, 2026)
The rapid growth of social media preachers (dai) in West Sumatra marks a significant transformation in the landscape of contemporary Islamic proselytization. Without formal certification, many young individuals use digital platforms such as YouTube, Instagram, and TikTok to deliver dakwah, even issuing complex Islamic legal opinions (fatwa). This phenomenon poses serious challenges regarding religious authority, fiqh accuracy, and Islamic legal literacy in digital spaces. This study aims to explore the extent to which millennial preachers apply Islamic legal literacy in their digital da'wah, how they construct religious authority among social media audiences, and how audiences respond to such da'wah content. Using a qualitative approach with digital ethnography as the methodological framework, data were collected through semi-structured in-depth interviews, content analysis of dakwah posts, and participant observation of live streaming interactions. Purposive sampling was employed to select da'i with significant followings focusing on Islamic legal content. Thematic analysis was applied with source triangulation to strengthen validity. The theoretical framework draws on media literacy theory, religious authority theory, cyber Islamic environments, and lumpen intelligentsia theory. Findings reveal wide variation in Islamic legal literacy among preachers, a shift in religious authority from institutional-epistemological bases to performative-digital ones, and paradoxical audience responses oscillating between appreciation and skepticism. This research contributes to understanding the transformation of Islamic dakwah in the digital era and proposes a hybrid dakwah model as a normative solution.